Effect of wettability on pool boiling heat transfer with copper microporous coated surface - Wang, Xiaomeng; Fadda, Dani; Godinez, Juan; Lee, Jungho; You, Seung M. (International Journal of Heat and Mass Transfer, 2022)
Microporous coated surfaces significantly enhance nucleate boiling heat transfer performance over plain surfaces. Pool boiling experiments are performed on a copper high-temperature, thermally-conductive, microporous coating (Cu-HTCMC) with altered surface wettability. The combined effect of surface wettability and microporous coating on nucleate boiling performance is experimentally investigated on copper surfaces. Specifically, the surface condition is pristine, oxidized, and Teflon-coated, yielding a surface wettability ranging between superhydrophilic (∼0° apparent contact angle) to hydrophobic (131° apparent contact angle). The experimental results show that the hydrophobic microporous surface promotes early bubble incipience, yielding a high heat transfer coefficient at low heat flux. However, with enhanced wettability, the hydrophilic microporous surfaces result in high critical heat flux. The enhanced wettability of the oxidized Cu-HTCMC surface offers a 19% increase in CHF (2350 kW/m2) over the pristine microporous surface, but the corresponding heat transfer coefficient for the pristine Cu-HTCMC surface (466 kW/m2K) is 37% higher than the oxidized. The trends are found to be consistent with plain copper surfaces, where the enhanced wettability (oxidized plain surface) offers a 57% increase in CHF over the pristine plain surface but h for the pristine is 9% higher at CHF.
Keywords: Apparent contact angle; Coated surface; Copper surface; Heat transfer co-efficients; Hydrophobics; Micro-porous surfaces; Microporous; Microporous coatings; Plain surfaces; Surface wettability; Critical heat flux; Microporous coating; Nucleate boiling; Wettability